Influence of national centralization of oesophagogastric cancer on management and clinical outcome from emergency upper gastrointestinal conditions. Issue 1 (20th November 2017) - Markar, S R; Mackenzie, H; Wiggins, T; Askari, A; Karthikesalingam, A; Faiz, O; Griffin, S M; Birkmeyer, J D; Hanna, G B
Abstract: Background: In England in 2001 oesophagogastric cancer surgery was centralized. The aim of this study was to evaluate whether centralization of oesophagogastric cancer to high-volume centres has had an effect on mortality from different emergency upper gastrointestinal conditions. Methods: The Hospital Episode Statistics database was used to identify patients admitted to hospitals in England (1997–2012). The influence of oesophagogastric high-volume cancer centre status (20 or more resections per year) on 30- and 90-day mortality from oesophageal perforation, paraoesophageal hernia and perforated peptic ulcer was analysed. Results: Over the study interval, 3707, 12 441 and 56 822 patients with oesophageal perforation, paraoesophageal hernia and perforated peptic ulcer respectively were included. There was a passive centralization to high-volume cancer centres for oesophageal perforation (26·9 per cent increase), paraoesophageal hernia (19·5 per cent increase) and perforated peptic ulcer (23·0 per cent increase). Management of oesophageal perforation in high-volume centres was associated with a reduction in 30-day (HR 0·58, 95 per cent c.i. 0·45 to 0·74) and 90-day (HR 0·62, 0·49 to 0·77) mortality. High-volume cancer centre status did not affect mortality from paraoesophageal hernia or perforated peptic ulcer. Annual emergency admission volume thresholds at which mortality improved were observed for oesophageal perforation (5 patients) and paraoesophageal hernia (11). Following centralization, the proportion of patients managed in high-volume cancer centres that reached this volume threshold was 88·0 per cent for oesophageal perforation, but only 30·3 per cent for paraoesophageal hernia. Conclusion: Centralization of low incidence conditions such as oesophageal perforation to high-volume cancer centres provides a greater level of expertise and ultimately reduces mortality. Abstract : Improves outcome of oesophageal perforation